Difficulties Quitting for Smokers with and without a Respiratory Disease and Use of a Tailored Intervention for Smoking Cessation – A Qualitative Study. (27th March 2017) - Alexis-Garsee, Camille; Gilbert, Hazel; Burton, Martha; van den Akker, Olga
Abstract : Introduction: Smokers with respiratory diseases are less likely to quit than those without impaired lung function, yet few studies have investigated the effectiveness of smoking cessation interventions with this population, and none have used a computer-tailored approach. Aims: This paper aims to fill this gap in the literature by exploring smokers' experiences when trying to quit and their perceptions of a computer-tailored intervention. Methods: Semi-structured interviews were conducted with 26 smokers recruited from six general practises in North London. Thematic analysis was conducted to examine participants' previous experiences of quitting and their perceptions of receiving personal tailored feedback reports to aid smoking cessation. Results: Participants discussed how their positive smoking experiences coupled with their negative cessation experiences led to conflicts with quitting smoking. Although the computer-tailored intervention was key in prompting quit attempts and participants valued its personal approach; it was not sufficient as a stand-alone intervention. Conclusions: The results highlight the difficulties that smokers experience when quitting and the need for a more personalised stop smoking service in smokers with respiratory diseases. The study also demonstrates the application and potential for computer-tailored intervention as part of a wider programme of long-term smoking cessation.